Comparison between Two Digital Panoramic Radiography Techniques for Proximal Caries Detection - Mina Shafagh Motlagh; Adineh Javadian Langaroodi; Seyed Hossein Hoseini Zarch (Mashhad University of Medical Sciences, 2013)
Introduction: Although proximal dental caries are very common, clinical examinations cannot detect them all. Panoramic radiography has been widely used in dentistry for both diagnosis and screening. This study aimed to investigate and compare the efficacy of two digital panoramic radiography techniques in the diagnosis of proximal caries. Methods: A total number of 60 patients referred to a dental radiology center, all had complete dental system and bitewing radiographies, were included. The patients were randomly divided into two groups of 30 patients. For the first and second groups, CR and DR images were obtained respectively. Images were obtained from the distal of the third tooth to the distal of the eighth. Bitewing images were compared with CR and DR images regarding the detection of caries. Kappa index and chi-squared statistics were employed to analyze the results. Results: There was a high agreement rate between bitewing images and CR (Kappa=0.775) and DR (Kappa=o.762) images in detecting caries. Also no significant difference was shown between CR and DR techniques in the detection of caries (0.543). However, DR and CR images are not efficient enough to be prescribed as the sole imaging technique to detect proximal caries. Conclusion: DR and CR techniques could be good imaging techniques for the detection of dental caries as a companion to clinical examinations.